O koordiniranih in večkratnih k-vprašanjih v slovenščini - Mišmaš, Petra (Jezik in slovstvo, 2017)
The article discusses multiple and coordinated wh-questions in Slovenian, focusing primarily on a comparison of the two based on the framework of generative grammar. On the basis of differences between coordinated and multiple wh-questions, we claim that, despite their superficial similarities, both groups need to be analysed separately in Slovenian as well. This conclusion is a starting point for further research of Slovenian coordinated wh-questions.
Keywords: Slovene; slovenščina; tvorbena slovnica; syntax; skladnja; koordinirana k-vprašanja; večkratna k-vprašanja